2023
DOI: 10.1021/acs.molpharmaceut.3c00140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anti-inflammatory Activity and Cellular Interaction of Brush Polymer–N-Acetyl Cysteine Conjugates in Human and Murine Microglial Cell Lines

Abstract: Microglia-mediated neuroinflammation is commonly associated with neurodegeneration and has been implicated in several neurological disorders, such as Alzheimer's disease and Parkinson's disease. Therefore, it is crucial to develop a detailed understanding of the interaction of potential nanocarriers with microglial cells to efficiently deliver anti-inflammatory molecules. In this study, we applied brush polymers as a modular platform to systematically investigate their association with murine (BV-2) and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…According to numerous studies, nanoparticles with higher aspect ratios have shown increased interaction with cell membranes. This is often attributed to their higher degree of accessible surface area, which provides more binding or association sites for interaction with cell membranes. In contrast, as previously observed with microglial cells, polymeric bottlebrush of ellipsoid shape with a length of 5.7 nm (M50-PEtOx 10 ) shows the highest interaction with hCMEC/D3 cells compared to elliptical worm-like chain polymers of 20.8 nm (M400-PEtOx 10 ) and 35.4 nm (M1000-PEtOx 10 or M1000-PEtOx 35 ) length. Based on previous studies, the wrapping time for elongated bottlebrush-like nanoparticles within the cells is longer than for ellipsoid/spherical nanoparticles due to their higher surface area.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…According to numerous studies, nanoparticles with higher aspect ratios have shown increased interaction with cell membranes. This is often attributed to their higher degree of accessible surface area, which provides more binding or association sites for interaction with cell membranes. In contrast, as previously observed with microglial cells, polymeric bottlebrush of ellipsoid shape with a length of 5.7 nm (M50-PEtOx 10 ) shows the highest interaction with hCMEC/D3 cells compared to elliptical worm-like chain polymers of 20.8 nm (M400-PEtOx 10 ) and 35.4 nm (M1000-PEtOx 10 or M1000-PEtOx 35 ) length. Based on previous studies, the wrapping time for elongated bottlebrush-like nanoparticles within the cells is longer than for ellipsoid/spherical nanoparticles due to their higher surface area.…”
Section: Resultsmentioning
confidence: 91%
“…17 As an initial assessment, we investigated the impact of the physical parameters of our polymeric brushes, including size and shape, on their brain endothelial cell association. A library of nonfunctionalized polymeric brushes with different sizes and shapes (M50-PEtOx 10 , M400-PEtOx 10 , M1000-PEtOx 10 , and M1000-PEtOx 35 ) prepared previously 16 was further exploited to understand the role of morphology on the interaction with brain endothelial cells before incorporation of the targeting ligand.…”
Section: Effect Of Size and Shape Of Nonfunctionalized Polymers On It...mentioning
confidence: 99%
See 3 more Smart Citations